Analysis of Using Canva Media to Enhance Poetry Writing Skills in Elementary School - Arifah, Mamik; Subrata, Heru; Istiq’faroh, Nurul (research, training and philanthropy institution Natural Aceh, 2024)
The biggest challenge experienced by elementary school teachers is instilling writing skills in their students. One alternative to improve writing skills is to write poetry. This research describes how elementary school students' poetry writing skills can be improved by using appropriate and interactive learning media such as Canva, which can facilitate elementary school students in developing creativity, imagination, and interest in writing poetry. This research uses descriptive qualitative methods with library study techniques. Data collection techniques using library research are carried out by searching for scientific articles that are relevant to the research. The scientific articles were obtained through the Garuda and Google Scholar databases for 2020-2024. There are 5 (five) articles taken and have been indexed by SINTA and national journal accreditation. Critical appraisal uses JIB, and data analysis uses a simplified approach. Based on the results of a study of 5 scientific articles, using the Canva application media can improve elementary school students' poetry writing skills to have a positive impact. Students are more interested and enthusiastic about participating in learning activities, making it easier for them to get inspiration for diction and express their creativity so they can develop imagination and creativity in writing poetry.